Digital Marketing in Agricultural Sector (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
The agriculture industry has the lowest percentage of content marketing adoption – 78% compared to the average 88% across all other industries. This is not to say that the agriculture sector is slow to adapt. Instead, it shows that non-digital tactics are more important in this industry. Many businesses in this sector still run successful content marketing campaigns, often using a mixture of online and offline techniques to provide something of value to their existing customers. The marketing of agricultural products is regarded as unique and deserve a special attention. The key objective of digital marketing is to promote brands, build preference and increase sales through various digital marketing techniques. In our survey, we wanted to show that digital marketing represents a huge opportunity for Agri-marketers. We took a sample on 200 student respondents to find out their knowledge about agricultural applications like Ag DNA, Agren Soil Calculator, AgriApp, Agric business, Agricultural chemicals, Agro Guide, Agri Market, Agricultural Policy Research, Climate App., Cropalyser, GPS Fields Area Measure, Organic Farming, Precision Agriculture, Tiger-Sul Nutrient CalculatorTiger-Sul Nutrient Calculator, Vrain, Vegetable farming, VRPETERS (Vehicle Rollover Prevention Education Training Emergency Reporting System), etc.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.